Bilateral Sturge Weber Syndrome- a rare case report - Singh, P; Singh, S (Nepalese Journal of Ophthalmology, 2013)
Background: Sturge-Weber syndrome is a rare congenital neuro- oculo- cutaneous disorder. Objective: To report a very rare unusual case of bilateral manifestation of Sturge Weber syndrome. Case: We report an unusual case of a 17-year-old female with advanced stage of bilateral glaucoma associated with facial nevus extending to the other half of the face as well and bilateral intracranial calcification. Conclusion: Sturge -Weber syndrome can manifest as a bilateral condition. Nepal J Ophthalmol 2013; 5(9):129-132 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7841